Life Cycle Assessment of a Commercially Available Organic Rankine Cycle Unit Coupled with a Biomass Boiler - Anna Stoppato; Alberto Benato (Energies, 2020)
Organic Rankine Cycle (ORC) turbogenerators are a well-established technology to recover from medium to ultra-low grade heat and generate electricity, or heat and work as cogenerative units. High firmness, good reliability and acceptable efficiency guarantee to ORCs a large range of applications: from waste heat recovery of industrial processes to the enhancement of heat generated by renewable resources like biomass, solar or geothermal. ORC unit coupled with biomass boiler is one of the most adopted arrangements. However, despite biomass renewability, it is mandatory to evaluate the environmental impact of systems composed by boilers and ORCs taking into account the entire life cycle. To this purpose, the authors perform a life cycle assessment of a commercially available 150 kW cogenerative ORC unit coupled with a biomass boiler to assess the global environmental performance. The system is modelled in SimaPro using different approaches. Results show that the most impacting processes in terms of CO2 equivalent emissions are the ones related to biomass production and organic fluid leakages with 71% and 19% of the total. Therefore, being fluid release in the environment high impacting, a comparison among three fluids is also performed. Analysis shows that adopting a hydrofluoroolefin fluid with a low global warming potential instead of the hydrocarbon fluid as already used in the cycle guarantees a significant improvement of the environmental performance.